2016
DOI: 10.1080/23120053.2016.1192808
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of antimicrobial stewardship concepts among final year pharmacy students in pharmacy schools across South Africa

Abstract: Background: Antimicrobial stewardship is currently not mandatory as part of the undergraduate training of pharmacists. Identifying gaps in knowledge and a better understanding of pharmacy students' perceptions about antimicrobial stewardship could assist in recommendations for appropriate changes to the pharmacy degree curricula that may lead to more appropriate use of antimicrobials, within the multidisciplinary team. Methods: A descriptive quantitative study with a survey design was conducted at the eight un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(77 citation statements)
references
References 8 publications
10
55
12
Order By: Relevance
“…This could be attributed to the fact that very few (17.1%) of the respondents in this study, had heard about ABS. Cotta et al (2014) reported that 41% have heard of antimicrobial stewardship (AMS) among practitioners (physicians, surgeons, pharmacists, anaesthetists, nurses) in a large private hospital in Australia while Burger et al (2016) reported that 83.5% have heard about AMS among final year pharmacy students in 3 South African universities. The differences in proportions of respondents that have heard of AMS in these studies, may be due to disparity in the level of AMS awareness education that has been conducted in the healthcare facilities/study area, awareness obtained from other sources (such as mass media, journals, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the fact that very few (17.1%) of the respondents in this study, had heard about ABS. Cotta et al (2014) reported that 41% have heard of antimicrobial stewardship (AMS) among practitioners (physicians, surgeons, pharmacists, anaesthetists, nurses) in a large private hospital in Australia while Burger et al (2016) reported that 83.5% have heard about AMS among final year pharmacy students in 3 South African universities. The differences in proportions of respondents that have heard of AMS in these studies, may be due to disparity in the level of AMS awareness education that has been conducted in the healthcare facilities/study area, awareness obtained from other sources (such as mass media, journals, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed after a literature review of comparable studies (Abbo et al, 2013;Burger et al, 2016;Castro-Sanchez et al, 2016) and validated by a pilot study on 10 veterinarians. Participation was voluntary.…”
Section: Data Collectionmentioning
confidence: 99%
“…[7] Similarly, a national survey was conducted in 2016 that focused on the knowledge and perceptions of antimicrobial stewardship concepts among finalyear pharmacy students in SA. [8] The results of the study revealed that although the majority (95.8%) of students felt that the implementation of antimicrobial stewardship programmes is essential, only 71.9% were familiar with stewardship programmes in SA, and 96.5% of participants stated that they would like more education on antimicrobial stewardship. [8] At the 37th annual general meeting of the Academy of Pharmaceutical Sciences of SA, held in July 2016, it was emphasised that steps need to be taken to ensure adequate undergraduate antimicrobial stewardship training for pharmacy students in SA.…”
Section: Undergraduate Antimicrobial Stewardship Training For Pharmacmentioning
confidence: 94%
“…[8] The results of the study revealed that although the majority (95.8%) of students felt that the implementation of antimicrobial stewardship programmes is essential, only 71.9% were familiar with stewardship programmes in SA, and 96.5% of participants stated that they would like more education on antimicrobial stewardship. [8] At the 37th annual general meeting of the Academy of Pharmaceutical Sciences of SA, held in July 2016, it was emphasised that steps need to be taken to ensure adequate undergraduate antimicrobial stewardship training for pharmacy students in SA. In response to the national call for undergraduate antimicrobial stewardship training for pharmacy students, a study is now being undertaken to develop a proposed minimum curriculum content suitable for implementation in undergraduate pharmacy degree programmes in SA.…”
Section: Undergraduate Antimicrobial Stewardship Training For Pharmacmentioning
confidence: 94%
“…Furthermore, undergraduate education is variable; a recent study of final-year pharmacy students across SA universities documented significant differences between the eight universities with regard to undergraduate AS education. [14] Furthermore, specialisation in pharmacy at a postgraduate level is not yet formally recognised by the South African Pharmacy Council and not widely available. With regard to nursing, the curriculum currently involves modules on microbiology and pharmacology.…”
Section: Importance Of Education and Trainingmentioning
confidence: 99%